Fructose Induces Insulin Resistance of Gestational Diabetes Mellitus in Mice via the NLRP3 Inflammasome Pathway - Liu, Yao; Wei, Yuanhuan; Wu, Lanlan; Lin, Xiaoping; Sun, Ruifang; Chen, Hengying; Shen, Siwen; Deng, Guifang (Frontiers in Nutrition, 2022)
Background: Insulin resistance (IR), which is affected by dietary factors, is the main pathology underlying of gestational diabetes mellitus (GDM). Fructose (Fru), a sugar found in fruits, honey and food sweeteners, has been reported to induce IR and inflammation. This study explored the effects and mechanisms of Fru on IR of GDM in pregnant and postpartum mice and their offspring. Methods: Six-week-old female C57BL/6J mice were randomly divided into control (Chow) and fructose (Fru) groups, with the latter receiving 20% (w/v) Fru in drinking water from 2 weeks before pregnancy to the end of pregnancy. The effects of Fru on IR and inflammation were determined using serum parameters, glucose metabolism tests, immunohistochemistry and western blotting. Results: Compared with the Chow group mice, pregnant mice treated with Fru exhibited greater gestational weight gain, higher fasting blood glucose and insulin concentrations and a higher homeostasis model of assessment (HOMA) for IR index, but a lower HOMA for insulin sensitivity index. Treatment with Fru also increased the concentrations of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), IL-17 and C-reactive protein in sera and the expression of IL-6, TNF-α, IL-17 and IL-1β mRNA in liver tissues of pregnant mice. Both CD68 and IL-1β positive cell were increased in Fru-treated mice compared with in Chow mice. Fru treatment also promoted IR and inflammation in mice at 4 weeks after delivery and in offspring mice. Mechanistically, Fru promoted the nuclear translocation of nuclear factor‐kappa B (NF‐κB) p65 to activate the nucleotide‐binding domain-like receptor protein 3 (NLRP3) inflammasome. Conclusions: Exposure to Fru before and during pregnancy induced IR in pregnant mice, which continued at 4 weeks postpartum and affected the offspring. The effects of Fru may be associated with activation of the NF-κB–NLRP3 pathway.